2022
DOI: 10.3389/fpsyg.2022.779986
|View full text |Cite
|
Sign up to set email alerts
|

Self-Efficacy and Professional Identity Among Freshmen Nursing Students: A Latent Profile and Moderated Mediation Analysis

Abstract: This study was designed to estimate the associations between self-efficacy and professional identity. A total of 1,051 freshmen nursing students (FNSs) from the Be Resilient to Nursing Career (BRNC) program were recruited from four universities between September and November 2020. A latent profile and moderated meditation analysis were performed. Four profiles of self-efficacy were identified and named as Lowest (15.6%), Med-low (45.0%), Med-high (32.7%), and Highest (6.7%). The mediating role of resilience an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(47 citation statements)
references
References 52 publications
4
42
1
Order By: Relevance
“…24 This scale has been successfully administered in previous studies. 14 16 The Cronbach's alpha was 0.875 in the present study.…”
Section: -Item Connor-davidson Resilience Scalesupporting
confidence: 49%
See 2 more Smart Citations
“…24 This scale has been successfully administered in previous studies. 14 16 The Cronbach's alpha was 0.875 in the present study.…”
Section: -Item Connor-davidson Resilience Scalesupporting
confidence: 49%
“…Second, mediation model showed that self-efficacy and resilience significantly mediated the relationship between neuroticism and psychological distress, indicating the important pathway of neuroticism → self-efficacy → resilience → psychological distress, which was also partially confirmed in Open access a previous study. 14 According to this pathway, theoretically, increasing self-efficacy and resilience could help reduce the impact of neuroticism on psychological distress. 34 Self-efficacy and resilience can be enhanced through specific programmes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Secondly, the power of model, such as role modelling [ 13 ] and the model of teacher [ 22 ] could improve students’ professional identity. Lastly, the students with higher self-efficacy and resilience have a higher level of professional identity [ 23 ]. However, there is a paucity of studies focusing on the influencing factors of nursing interns’ professional identity during clinical internship.…”
Section: Introductionmentioning
confidence: 99%
“…A total of 613 nursing students were approached from Be Resilient to Nursing Career (BRNC) between October and December 2021. 2 , 22 A total of 595 completed the booklet resulting in a response rate of 97.1%. A sample size of 500 provides good test power and convergent validity for the model indicators.…”
Section: Methodsmentioning
confidence: 99%